INCREASED ATTRACTION OF ORYCTES RHINOCEROS AGGREGATION PHEROMONE, ETHYL 4-METHYLOCTANOATE, WITH COCONUT WOOD - Ambrosio Raul R. Alfiler (International Coconut Community, 1999)
Trapping experiments at the Zamboanga Research Center of the Philippine Coconut Authority provided evidence of the resultant synergistic activity of the combination of the Oryctes rhinoceros aggregation pheromone, Ethyl 4-methyloctanoate, and old coconut wood in pheromone traps. Traps containing both old coconut wood and aggregation pheromone caught significantly more rhinoceros beetles than traps containing the pheromone or old coconut wood alone. The use of selective trapping using the aggregation pheromone presents a new option for the reduction of the beetle population in the field and control of this important pest of coconut palm in the Philippines.